1999
DOI: 10.1111/j.1600-0714.1999.tb01996.x
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemical expression of p53, MDM2, Ki‐67 and PCNA in central giant cell granuloma and giant cell tumor

Abstract: Central gaint cell granuloma (CGCG) is a reactive bone lesion that occurs mainly in the jaws. The gaint cell tumour (GCT) is a benign locally aggressive neoplasm located near the articular end of tubular bones. Both lesions are characterised histologically by multinucleated gaint cells in a background of ovoid to spindle‐shaped mesenchymal cells. There is a basic question whether both lesions are separate entities or variants of the same disease. The study of cell cycle‐associated proteins may give insights in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
44
0
6

Year Published

2000
2000
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(52 citation statements)
references
References 30 publications
2
44
0
6
Order By: Relevance
“…These metastatic tumours show less expression of the proliferation marker Ki-67 than continuous slow-growing and rapidly growing metastases. Other studies, however, have reported no consistent difference in the mitotic index [1,2,15] or in expression of proliferation and other tumour markers in primary and recurrent GCTBs associated with lung metastasis [21][22][23][24][25]. We noted that the immunophenotype of giant cells in primary (non-metastatic and metastatic) GCTBs and lung nodules was identical, indicating that the osteoclasts are essentially reactive cells recruited by receptor activator of nuclear factor-κB ligandexpressing mononuclear stromal cells [13]; the role of osteoclast specific proteases, such as cathepsin K [26], in lung nodule formation has not been determined, but it would be expected that this enzyme would be similarly expressed by osteoclasts in primary and secondary GCTBs.…”
Section: Discussionmentioning
confidence: 96%
“…These metastatic tumours show less expression of the proliferation marker Ki-67 than continuous slow-growing and rapidly growing metastases. Other studies, however, have reported no consistent difference in the mitotic index [1,2,15] or in expression of proliferation and other tumour markers in primary and recurrent GCTBs associated with lung metastasis [21][22][23][24][25]. We noted that the immunophenotype of giant cells in primary (non-metastatic and metastatic) GCTBs and lung nodules was identical, indicating that the osteoclasts are essentially reactive cells recruited by receptor activator of nuclear factor-κB ligandexpressing mononuclear stromal cells [13]; the role of osteoclast specific proteases, such as cathepsin K [26], in lung nodule formation has not been determined, but it would be expected that this enzyme would be similarly expressed by osteoclasts in primary and secondary GCTBs.…”
Section: Discussionmentioning
confidence: 96%
“…Individual genes included in the Wnt pathway influence the destructivity of GCTB and promote cell growth. It is widely known that b-catenin has an important role in the Wnt signaling pathway, as well as in the incidence of numerous primary mesenchymal tumors of bone and soft tissue [11,12,13,14].…”
Section: Discussionmentioning
confidence: 99%
“…4 TP53 overexpression as an indicator of TP53 mutation has been correlated with lung metastasis and recurrence of giant cell tumour of bone according to some but not all observers. [18][19][20] The cell-cycle regulator protein, CCND1, together with CDKN1A, both of which have a regulatory role in centrosome reduplication, has also been reported to be overexpressed in the giant cell component of giant cell tumour of bone. [21][22] A possible role of the oncogene MYCC has also been suggested in the pathogenesis of this tumour by Gamberi et al, 23 who found that MYCC was overexpressed in both the giant cell and mononuclear cell populations of metastatic cases of giant cell tumour of bones.…”
Section: Discussionmentioning
confidence: 99%